2022
DOI: 10.3390/pr10050805
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of an Elliptical Squirmer

Abstract: In this paper the propulsion of elliptical objects (called squirmers) by imposed tangential velocity along the surface is studied. For a symmetric velocity distribution (a neutral squirmer), pushers (increased tangential velocity on the downstream side of the ellipse) and pullers (increased tangential velocity on the upstream side of the ellipse), the hydrodynamic characteristics, are simulated numerically using the immersed boundary-lattice Boltzmann method. The accuracy of the numerical scheme and code are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This is especially true for lattice Boltzmann method, where, after all, it is a relatively straightforward task to modify the 2D code to handle 3D simulations. In addition, previous studies [38,39,42,43,45,46] have shown that the essence of the phenomenon remains unchanged even when the dimensionality is reduced. Moreover, comparing 2D simulation results with 3D simulation results can also help us to understand the effect of dimensionality.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This is especially true for lattice Boltzmann method, where, after all, it is a relatively straightforward task to modify the 2D code to handle 3D simulations. In addition, previous studies [38,39,42,43,45,46] have shown that the essence of the phenomenon remains unchanged even when the dimensionality is reduced. Moreover, comparing 2D simulation results with 3D simulation results can also help us to understand the effect of dimensionality.…”
mentioning
confidence: 97%
“…Zantop and Stark [41] constructed a claviform squirmer by linearly arranging several spherical squirmers and introduced a new velocity model. Liu et al [42] used an immerged-boundary-lattice Boltzmann method based on a circular squirmer model and a conformal-mapping technique to numerically simulate the hydrodynamic characteristics of elliptical squirmers. They found that as the Re increases, the swimming velocity of the pusher increases monotonically, whereas the swimming velocity of the puller first decreases and then increases.…”
mentioning
confidence: 99%